Interpretation of the Qur'an from Classical-Textual to Contemporary-Contextual; An Approach Proposed by Muslim Scholars - Ridho, Hilmi; Sabil, Afif; Firmansyah, Mohammad; Mukhlis, Febri Hijroh; Khairi, Aizat (QiST: Journal of Quran and Tafseer Studies, 2025)
The purpose of this study is to examine the thoughts of contemporary Muslim scholars who offer a contextual approach to understanding the Qur'anic text and the theoretical relationship of each of these figures' thoughts and their application in Q.S. al-Maidah: 38. Some of the statistics discussed in this study include: Fazlur Rahman, Abdullah Saeed, Khaled Aboe El-Fadl, and M. Amin Abdullah. The selection of these four figures was based on the strength of their thinking in understanding the contextual nature of the Qur'an and their influence on other contemporary Muslim scholars, both in Indonesian Islamic universities and in different countries. By formulating the thoughts of these four figures, a moderate contemporary interpretation of Islamic law will be formed, and laws that are relevant to the realities of the times will be formulated. This research uses a literature approach by reviewing literature journals and contemporary tafsir books. The primary data of this research are books and journals that are the thoughts of the four figures, especially those that discuss the hermeneutics of the Qur'an in the renewal of Islamic studies. This research concludes that the contemporary interpretations of the four figures have similarities in seeing the social realities that occur and their theories are interconnected with each other. Fazlur Rahman's double movement theory plays a role in seeing Khaled Aboe El-Fadl's theory's relationship between author, text, and reader. Abdullah Saeed's hierarchy of values theory plays a role in mapping the text. The three-element theory (text, reality, insight) of M. Amin Abdullah serves as a measure of a reader's insight in analyzing the text and connecting it with the reality that occurs. According to them, the punishment for cutting hands contained in Q.S. al-Maidah: 38 can be replaced with imprisonment or a heavy fine. This is because the punishment of cutting hands is no longer by the current social reality, considered inhumane, and contrary to humanity. This research remains theoretical in nature. Future studies may apply the proposed contextual framework to other Qur'anic themes, such as socio-legal or ethical issues, to test its broader applicability.